Optimization of hexagonal boron-doped silicate photonic crystal fiber to obtain near zero flattened dispersion for nonlinear waves by finite difference method - Tiwari, Subhashish; Vyas, Ajay Kumar; Pandey, Atul; Kumar, Rajesh; Pandey, Praveen Chandra; Dixit, Achyutesh (Springer, 2022)
The B2O3-doped silicate photonic crystal fber (PCF) containing small core and dielectric rods built of lead silicate SF57 has been most intensively explored for diverse pump signals centered at a 0.65 µm, communication band. This type of doping has been carried out to diminish the upgraded refractive index of silica by a signifcant amount. This enhances special capabilities that lead to an outstanding potential to PCF for the profoundly intense feld in the optical Kerr efect. In this study, the mode analysis has been done by solving a nonlinear wave equation for a Gaussian input beam using the fnite diference method under analytical boundary conditions. Numerical results show that due to ultra-low changes in nonlinear behaviour, extremely small doping of B2O3 is needed to enable sustained confnement of a beam with fattened dispersion.
Keywords: Dispersion; · Finite diference time domain method; Nonlinearity; · Photonic crystal fber